Critical flicker frequency measurement training - V. V. Rozhentsov (Oftalʹmologiâ, 2014)
Purpose: Developing a method to improve the accuracy of the measuring of critical flicker frequency (CFF).Methods: When measuring CFF the light pulses with LEDs yellow 5 mm in diameter with a force of light 3 mcd placed in an area near point of clear vision. Formation of light pulses and measuring CFF was performed using PC Pentium III by the method of successive approximation. Measured CFF value was noted on the plane in the coordinates «CFF value — the number of measurement», a graph of CFF values was drawn as a function F = f (Ni), where Ni — number of i-th measurement, i = 1, 2,…, k, k — number of measurements to obtain a quasi-stationary mode when the transition process is completed. In the quasi-stationary mode we were performed a specified number of measurements and then calculated the CFF estimate as the mean value of test results obtained in the quasi-stationary mode.Results: Reducing the random component of the CFF measurement error of study group of 10 pre-trained subjects was received in 8 of them and varies from 31.3 to 78.6 %.Conclusion: Analyzing the dynamics of CFF values obtained during its measurement and performing a statistical analysis of the measurements obtained in the quasi-stationary mode, we can improve the accuracy of CFF estimate.